(untitled) (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
Digital transformation is a systemic shift that affects various aspects of human life, including social mobility in rural communities. Digital technologies offer new opportunities for access to education, information, and employment that were previously limited for people living in rural areas. However, not all individuals are equally able to take advantage of these opportunities. From the perspective of philosophical anthropology, particularly through the understanding of humans as thinking beings (homo sapiens) and free beings (homo liberum), digital transformation requires reflective thinking, autonomy in decision-making, and moral responsibility in the use of technology. Social mobility is not merely seen as material movement between social classes but also as the actualization of human potential within the digital space. Therefore, the role of technology in supporting rural life greatly depends on the extent to which individuals can think critically, adapt meaningfully, and regard technology as a means to achieve a more meaningful and dignified existence. This abstract highlights that digital transformation, when integrated with human values and philosophical reflection, can serve as an ethical and functional instrument in promoting inclusive and dignified social mobility in rural communities.